AIMP1 Mutation Long-Term Follow-Up, With Decreased Brain N-Acetylaspartic Acid and Secondary Mitochondrial Abnormalities. (21st February 2019) - Khan, Aneal; Bennett, Jennifer; Scantlebury, Morris H.; Wei, Xing-Chang; Kerr, Marina
Aminoacyl transfer RNA (tRNA) synthetase complex-interacting multifunctional protein I is a noncatalytic component of tRNA multi-synthetase complexes. Although important in joining tRNAs to their cognate amino acids, AIMP1 has several other functions including axonal growth, cytokine activity, and interactions with N -acetylaspartic acid in ribosomal tRNA synthetase complexes. Further, N -acetylaspartic acid donates an aspartate during myelination and is therefore important to axonal integrity. Mutations in AIMP1 can disrupt these functions, as demonstrated in this clinical case study of 2 monozygotic twins, who display congenital opisthotonus, microcephaly, severe developmental delay, and seizures. Whole exome sequencing was used to identify a premature stop codon in the AIMP1 gene (g. 107248613_c.115C>T; p.(Gln39). In the absence of whole exome sequencing, we propose that decreased N -acetylaspartic acid peaks on magnetic resonance spectroscopy could act as a biomarker for AIMP1 mutations.